(untitled) (Revista Científica Compendium, 2024)
In order to define the corporate communication model for the development of post-conventional management in the Venezuelan public university, this research was carried out using a qualitative methodological field approach, applied to a homogeneous, probabilistic and random sample, made up of nine key informants: three workers from the blue-collar staff, three from the administrative staff and three teachers from three universities in the state of Lara. The analysis of the information allowed us to detect that in these educational institutions communication is vertical, without active participation of the staff, which is why comprehensive corporate communication is considered necessary, in which all its members are included, both in decision-making, through intra-communication on the network; and an organizational or internal organic communication that shows the being and the doing of the institution, in order to strengthen the corporate identity, build a shared vision and originate a post-conventional university management that responds to the new reality of the 21st century that surrounds it and in which the university is immersed.